Perception and Use of E-Collaboration by Postgraduate Students in Nigeria Universities - Tella, Adeyinka (IJIE (Indonesian Journal of Informatics Education), 2023)
Collaboration in the Nigerian context has focused majorly on traditional collaboration and not even among postgraduate (PG) students. Advancement in technology has ushered many changes, particularly the introduction of numerous e-tools for collaboration. It is based on this that the study examined the perception and use of e-collaboration by postgraduate students in Nigeria Universities. The study adopted a survey design using a questionnaire to collect data from 631 postgraduate students selected across ten universities in South-West Nigeria. Six objectives were developed to guide the study. The results revealed that e-collaboration is perceived by postgraduate students as a collaboration among individuals engaged in a common task using electronic technologies. E-collaboration is used mostly for projects and research and it is impactful in providing opportunities to interact better than face- to-face collaborative activities. The study revealed electronic mail, social media including (Facebook, Twitter, and WhatsApp), discussion forums and Google documents as the tools most significantly used for e-collaboration. The reasons why respondents use e-collaboration include flexibility, availability, and compatibility with cell phones. The level of awareness about the ethics of e- collaboration is reported to be too low. However, a small percentage were aware that participation in decision-making and the sharing of blame and credit for outcomes is the responsibility of all members. Challenges faced by PG students in their e- collaboration efforts are power failure, lack of trust, and poor internet connection and speed. It is recommended that more awareness of e-collaboration should be promoted and coupled with improved internet connectivity.